Physicochemical and Organoleptic Properties of Analog Rice from White Corn Flour and Canna Starch with Glycerol Monostearate Addition - Jariyah Jariyah; Dianita Kumalasari; Ratna Yulistiani; Salmaa Mardhotillah (AgriHealth: Journal of Agri-food, Nutrition and Public Health, 2025)
Indonesia’s reliance on rice as a staple food is challenged by declining harvested areas, highlighting the need for alternative carbohydrate sources. Analog rice made from white corn flour (WCF) and canna starch (CS), with glycerol monostearate (GMS) as a texture modifier, offers a potential solution to promote food diversification and reduce dependence on conventional rice. The purpose of this study was to determine the ideal WCF–CS ratio and GMS level. This study employed a completely randomized design with two factors: the WCF to CS ratios (60:40, 70:30, 80:20) and the addition of GMS (2%, 3%, 4%), each replicated three times. Analog rice was prepared through a process of mixing, steaming, extrusion, and drying. Physicochemical properties (moisture, ash, protein, carbohydrate, starch, amylose, amylopectin, rehydration, bulk density, and cooking time), as well as sensory attributes, were analyzed using analysis of variance (ANOVA) followed by Duncan’s multiple range test (DMRT) at a 5% significance level. The formulation containing 70% WCF, 30% CS, and 3% GMS yielded the most desirable product with 0.67 g ml-1 of bulk density, 98.27% of rehydration ability, 207.67 seconds of cooking time, 7.02% of moisture, 0.46% of ash, 0.24% of fat, 6.47% of protein, 85.82% of carbohydrate, 77.28% of starch, 26.45% of amylose, and 50.84% of amylopectin. The results of the organoleptic scores for color, taste, texture, and aroma were 3.12, 3.52, 3.84, and 3.60, respectively. This research highlights the potential of local carbohydrate sources such as corn and canna for analog rice production to support national food diversification.